Genetic Variants of DNA Repair Genes as Predictors of Radiation-Induced Subcutaneous Fibrosis in Oropharyngeal Carcinoma - Gupta, Ankita; Mathew, Don; Bhat, Shabir Ahmad; Ghoshal, Sushmita; Pal, Arnab (Frontiers in Oncology, 2021)
Purpose: To investigate the impact of genetic variants of DNA repair and pro-fibrotic pathway genes on the severity of radiation-induced subcutaneous fibrosis in patients of oropharyngeal carcinoma treated with radical radiotherapy. Materials and Methods: Patients of newly diagnosed squamous cell carcinoma of oropharynx being treated with two-dimensional radical radiotherapy were enrolled in the study. Patients who had undergone surgery or were receiving concurrent chemotherapy were excluded. Patients were followed up at 6 weeks post completion of radiotherapy and every 3 months thereafter for a median of 16 months. Subcutaneous fibrosis was graded according to the Radiation Therapy Oncology Group (RTOG) and the European Organization for Research and Treatment of Cancer (EORTC) grading system and the maximum grade was recorded over the length of the patient’s follow-up. Patients with severe fibrosis (≥G3), were compared to patients with minor (≤G2) fibrotic reactions. Eight single nucleotide polymorphisms of 7 DNA repair genes and 2 polymorphisms of a single pro-fibrotic pathway gene were analyzed by Polymerase Chain Reaction and Restriction Fragment Length Polymorphism and were correlated with the severity of subcutaneous fibrosis. Results: 179 patients were included in the analysis. Subcutaneous fibrosis was seen in 168 (93.9%) patients. 36 (20.1%) patients had severe (grade 3) fibrosis. On multivariate logistic regression analysis, Homozygous CC genotype of XRCC3 (722C>T, rs861539) (p=0.013*, OR 2.350, 95% CI 1.089-5.382), Homozygous AA genotype of ERCC4 Ex8 (1244G>A, rs1800067) (p=0.001**, OR 11.626, 95% CI 2.490-275.901) and Homozygous TT genotype of XRCC5 (1401G>T, rs828907) (p=0.020*, OR 2.188, 95% CI 1.652-7.334) were found to be predictive of severe subcutaneous fibrosis. On haplotype analysis, the cumulative risk of developing severe fibrosis was observed in patients carrying both haplotypes of variant Homozygous (AA) genotype of ERCC4 Ex8 (1244G>A, rs1800067) and Homozygous (TT) genotype of XRCC5 (1401 G>T, rs828907) (p=0.010*, OR 26.340, 95% CI 4.014-76.568). Conclusion: We demonstrated significant associations between single nucleotide polymorphisms of DNA repair genes and radiation-induced subcutaneous fibrosis in patients of oropharyngeal carcinoma treated with radiotherapy. We propose to incorporate these genetic markers into predictive models for identifying patients genetically predisposed to the development of radiation-induced fibrosis, thus guiding personalized treatment protocols.